Recent advancements to enhance the therapeutic efficacy of antiepileptic drugs - Li Fuquan; Singh Akhilesh Vikram (Acta Pharmaceutica)
Epilepsy is a multifactorial neurological disorder characterized by recurrent or unprovoked seizures. Over the past two decades, many new antiepileptic drugs (AEDs) were developed and are in use for the treatment of epilepsy. However, drug resistance, drug-drug interaction and adverse events are common problems associated with AEDs. Antiepileptic drugs must be used only if the ratio of efficacy, safety, and tolerability of treatment are favorable and outweigh the disadvantages including treatment costs. The application of novel drug delivery techniques could enhance the efficacy and reduce the toxicity of AEDs. These novel techniques aim to deliver an optimal concentration of the drug more specifically to the seizure focus or foci in the CNS without numerous side-effects. The purpose of this article is to review the recent advancements in antiepileptic treatment and summarize the novel modalities in the route of administration and drug delivery, including gene therapy, for effective treatment of epilepsy.